Study of surface morphology, structure, mechanical and tribological properties of an AlSiN coating obtained by the cathodic arc deposition method. (September 2017) - Petkov, Nikolay; Bakalova, Totka; Cholakova, Tetiana; Bahchedzhiev, Hristo; Louda, Petr; Ryšánek, Petr; Kormunda, Martin; Čapková, Pavla; Kejzlar, Pavel
Abstract: AlSiN coatings were prepared by the cathodic arc deposition method at a temperature of 400 °C and pressure of 2.6 Pa. The chemical composition, determined by SEM/EDS analysis, shows that the AlSiN coating presented here has a stoichiometry structure (Al40 Si9 N51 ). XPS and XRD analyses indicated AlN in both cubic and hexagonal modifications in the coating, and that the coating has a not fully completed nanocomposite structure. Nanoindentation measurements indicate nanohardness and elastic modulus of 39 GPa and 389 GPa, respectively. The coating has a very good adhesion strength with an average critical load of 28.3N (first cohesive failure) and 62.3N (first adhesion failure). The estimated wear rate and coefficient of friction of the coating are 27.2 × 10 −6  mm 3  N −1  m −1 and 0.7, respectively (using the friction pair AlSiN/Al2 O3 ). Highlights: The AlSiN coatings have high hardness (39 GPa) and high wear resistance. In the coating is indicated AlN in both modifications: cubic and hexagonal; the coating has a nanocomposite structure. AlSiN coating are suitable for covering cutting tools for machining and cutting of steel parts.